Prediction of the bone volume for sinus augmentation through 3-dimensional analysis - Su-Yun Park; Kwang-Min Kim; Yu-Jin Kim; Jae-Rim Lee; Ho Lee; Yoon-Sic Han (Elsevier, 2024)
Background/purpose: No consensus has been established regarding the exact amount of bone grafting in maxillary sinus augmentation. The aim of this study was to estimate the minimum bone volume for sinus augmentation and to investigate the factors that influence the augmentation volume (AV). Materials and methods: This study included patients with cone-beam computed tomography scanning. Dome-shaped sinus augmentation was performed virtually at vertical heights (VH) of 3, 5, 7, and 9 mm in Group A (without implantation) and Group B (with implantation). The augmentation angle (AA) and the sinus width (SW) were measured. The AV was measured using the three-dimensional image processing program 3D Slicer. Univariable and multivariable analyses were conducted. Results: This study included 30 patients (120 subjects). In Group A, the mean AVs were 0.062, 0.271, 0.642, and 1.287 cc at VHs of 3, 5, 7, and 9 mm, respectively, in Group B, the mean AVs were 0.037, 0.230, 0.594, and 1.230 cc. Univariable analysis indicated that factors significantly associated with the AV in both groups included SW, AA, and VH (P < 0.001). Multivariable analysis indicated that factors significantly associated with the AV in both groups included AA and VH (P < 0.01). Conclusion: Clinicians can predict the bone volume for sinus augmentation by measuring the augmentation height and angle.